T-helper cells as new players in ANCA-associated vasculitides - Abdulahad, Wayel H (BioMed Central, 2011)
In anti-neutrophil cytoplasmic autoantibody-associated vasculitides (AAV), several observations support a key role of T-helper cells (CD4(+ )T cells) in disease pathophysiology. An expanded population of effector memory CD4(+ )T cells in AAV patients may contribute to tissue injury and disease progression. In addition, functional impairment of regulatory T cells (T(Regs)) is reported in AAV patients. A fraction of T(Regs )have the capacity to differentiate into Th17 cells in the context of a proinflammatory environment. Therefore, nonfunctionality of T(Regs )described in AAV patients may be caused by their conversion into IL-17-producing cells that may contribute to granulomatous vasculitis. Further investigations directed at the plasticity of T(Regs )in AAV patients are warranted.